Kvantifikacija občinstev kot ključni dejavnik odločanja v spletnih uredništvih - Slaček Brlek, Aleksander Sašo (Javnost (Ljubljana), 2014)
Using the methods of content analysis and in-depth interviews the author analyses the three most visited Slovene news sites (24ur.com, Planet Siol and MMC RTV SLO) to answer the following research questions: 1. What is the connection between the measured attention of the audience and the placement of news items on the webpages; and 2. How do editors perceive the use of methods of quantifying audiences and results of public opinion polls in their work. The content analysis revealed that 24ur.com was the most specific case in the analysed time-period, because it focused almost exclusively on the most popular topic at the time. The analysis of interviews showed that the number of clicks is the most important quantitative resource that influences the work of editors. They view poll results primarily as an interesting news item and not as a relevant factor in editorial decision making.
Keywords: mass media; množični mediji; informiranje; svetovni splet; spletni portali; urejanje; uredniki; odločanje